DENMARK IMPLEMENTATION OF EUROPEAN UNION RENEWABLE ENERGY POLICY IN PARIS AGREEMENT TO FACE THE THREAT GLOBAL WARMING - Amangku, Hisao (Universitas Nasional, 2025)
Global warming, driven predominantly by greenhouse gas emissions from fossil fuels, presents a critical environmental challenge. The European Union (EU) has introduced frameworks such as the European Green Deal (EGD) to foster climate neutrality by 2050, with Denmark emerging as a frontrunner in renewable energy adoption. This study investigates how Denmark operationalizes the EGD’s objectives, focusing on renewable energy initiatives and their efficacy in mitigating climate impacts. Employing a qualitative methodology, the research analyzes policy documents, national strategies, and secondary literature to evaluate Denmark’s alignment with EU directives, including the Renewable Energy Directive (RED), and international commitments like the Paris Agreement. Key findings reveal Denmark’s significant progress in reducing emissions by 50% since 1990, primarily through large-scale investments in wind energy—contributing over 40% of national electricity—and solar power integration. Policy mechanisms such as feed-in tariffs, carbon taxation, and cross-sectoral partnerships have accelerated green technology adoption. Infrastructure innovations, including offshore wind farms and district heating systems, further underscore Denmark’s sustainable transition. However, challenges persist in decarbonizing agriculture and transportation, which account for 30% of emissions, necessitating enhanced electrification and behavioral shifts. The study concludes that Denmark’s success stems from robust policy coherence, public-private collaboration, and long-term regulatory stability, offering a replicable model for nations pursuing climate resilience. While Denmark’s achievements highlight the feasibility of EGD targets, scaling such strategies globally requires context-specific adaptations, particularly in developing economies. Future research should explore transferability barriers and sector-specific solutions to address residual emission hotspots.